Report of the Committee on Professional Examinations. - Kistler, Linda H.; Bulloch, James; Smith, Kenneth A.; Sweeney, Daniel L.; Austin, Walter G.; Delaney, Patrick R.; Flowers, W. Baker; Mead, George C.; Smith, Ralph E.; Engler, Calvin; Hendrickson, Harvey S.; Winkle, Gary M. (The Accounting Review, 1976)
Abstract Focuses on a project by the American Accounting Association's Committees on Professional Examinations which evaluated the professional examinations for accountants. Objectives of the project; Methodology of the projects; Comparison of examinations and accounting curricula; Recommendations.